Simulation-Based Investigation of the Heat Exchange Within a Partial Hot Stamping Process - Reihani, Alborz; Badroosian, Darwin; Heibel, Sebastian; Schweiker, Thomas; Merklein, Marion (Lecture Notes in Mechanical Engineering, 2024)
Studies on crash performance show that hot stamped components with homogeneous mechanical properties can reach their limits in highly stressed car body areas. To face this challenge, hot stamped components can be optimized by integrating ductile areas. A suitable technology for adjusting tailored properties is based on a special furnace chamber within a multi-chamber furnace in which a cooled aluminum mask protects the blank locally from incident heat radiation. Simultaneously, the mask absorbs the blank’s own radiation. In addition to the temperature and radiation properties, this heat exchange depends in particular on the orientation and position of the radiating surfaces in the furnace chamber. For this reason, the mask distance to the blank can influence the width and characteristics of the transition zone after partial hot stamping. In order to predict the correlation between hard and ductile area, the process of partial hot stamping with varying mask distances is modelled in LS-DYNA® and validated experimentally. The results indicate that it is feasible to simulate the influence of the mask distance on the resulting hard, soft and transition zone after partial hot stamping. Furthermore, the results demonstrate that transition zones on a partially hot stamping part can be designed more flexibly, thus extending the limits in terms of part complexity.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Finite-Element Simulation; Heat Treatment; Hot Stamping; Tailored Properties